Dynamic control analysis of eco-efficient double side-stream ternary extractive distillation process. (April 2021) - Zhang, Qingjun; Hou, Wei; Ma, Youguang; Yuan, Xigang; Zeng, Aiwu
Highlights: Dynamic control analysis of eco-efficient double side-stream ternary extractive distillation process is studied. A newly robust control scheme is developed that handles the large step disturbances. Dynamic control performance is improved by using the composition control loops. Good product compositions controls are achieved without any product offsets. Abstract: The novel contribution of this paper is to implement the dynamic control investigation for the energy-saving double side-stream ternary extractive distillation configuration with constructing the practical and workable plumbing arrangement taking the representative example of separating a ternary benzene/isopropanol/water mixture. The new proposed control scheme achieves the stable regulatory control at rejecting the large disturbances of throughput and feed composition, wherein the particularly key control loops are controlling the product isopropanol composition by adjusting the extractant flow rate into extractive column C2 with simultaneously regulating the reflux ratio in extractive column C1 to abate the solvent dilution effect through composition cascade temperature control loops. Graphical abstract: Image, graphical abstract